Development of a Malaysian undergraduate geriatric medicine curriculum - Sallehuddin, Hakimah; Tan, Maw Pin; Blundell, Adrian; Gordon, Adam Lee; Masud, Tahir (Full Universe Integrated Marketing, 2020)
Background/Purpose: Malaysia is only beginning to age in 2020, but is expected to do this at an unprecedented rate in the next two decades. We aim to develop a national curriculum for undergraduate geriatric medicine in Malaysia to ensure future doctors are adequately equipped to address the healthcare needs of our older population. Methods: The draft curriculum was developed by the Malaysian Society of Geriatric Medicine through literature review and mapping to the Malaysian Accreditation Guidelines for Undergraduate Medical Programme 2015. The curriculum was then refined through a modified Delphi process which involved 15 expert panel members each from Malaysia, Australia and the United Kingdom. Results: A total of three Delphi rounds were conducted. Five out of seven invited panellists agreed to participate in the first Delphi round. A larger group was invited via e-mail and fifteen panellists agreed to participate in Delphi rounds two and three, which resulted in 75 and 15 comments respectively. The final document with 34 learning outcomes was accepted with 80% agreement and consisted of detailed objectives grouped under 10 overarching core topics. Conclusion: Following consensus agreement determined through a Delphi process, a Malaysian undergraduate curriculum for geriatric medicine, aligned with the Malaysian Accreditation Guidelines, has been developed and will be shared with the 32 medical colleges in Malaysia to determine the current level of, and barriers to delivery.